Efektivitas Kegiatan Sosialisasi Peraturan Wali Kota Palangka Raya Nomor 5 Tahun 2026 yang Diselenggarakan oleh BKAD Kota Palangka Raya - Muhammad Hafizd Riandi; Aprilita Aprilita (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
This study aims to analyze the effectiveness of the socialization activity of Mayor Regulation of Palangka Raya Number 5 of 2026 concerning Domestic Official Travel Guidelines organized by the Regional Financial and Asset Agency (BKAD) of Palangka Raya City. This study employed a qualitative approach with a descriptive research type. Data were collected through interviews, observation, and documentation, while data analysis used the Miles and Huberman model. The analysis applied Duncan’s effectiveness theory in Steers (1985), which includes goal attainment, integration, and adaptation. The results showed that the socialization activity had been quite effective in improving officials’ understanding of official travel administration. From the goal attainment aspect, the activity helped reduce administrative errors and improve participants’ understanding of official travel regulations. From the integration aspect, communication between speakers and participants was considered effective through presentations, discussions, and interactive coordination. From the adaptation aspect, participants were generally able to implement the new provisions, although several technical obstacles and the need for further assistance were still found. Thus, the socialization activity had a positive impact on improving orderly official travel administration within the Palangka Raya City Government environment, although it still needs to be strengthened through periodic socialization and technical assistance activities.